2017
DOI: 10.1007/s00415-017-8657-y
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral carotid cavernous sinus fistula: a case report and review of the literature

Abstract: Carotid cavernous fistula (CCF) is an abnormal vascular shunt from the carotid artery to the cavernous sinus. They are commonly classified based on hemodynamics, etiology or anatomically. Hemodynamic classification refers to whether the fistula is high or low flow. Etiology is commonly secondary to trauma or can occur spontaneously in the setting of aneurysm or medical conditions predisposing to arterial wall defects. Bilateral carotid cavernous fistulas are rare. We present a case of bilateral CCF secondary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
0
22
0
3
Order By: Relevance
“…CCFs can be classified based on haemodynamics (high flow vs low flow), anatomy (direct vs indirect/dural) or aetiology (traumatic vs spontaneous). Previous reports have identified that greater than 75% of all CCFs are secondary to trauma 2–4. The mechanism is thought to be due to shear forces, or by direct damage sustained from bony injuries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CCFs can be classified based on haemodynamics (high flow vs low flow), anatomy (direct vs indirect/dural) or aetiology (traumatic vs spontaneous). Previous reports have identified that greater than 75% of all CCFs are secondary to trauma 2–4. The mechanism is thought to be due to shear forces, or by direct damage sustained from bony injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, dural CCFs arise secondary to systemic diseases including hypertension, Ehlers-Danlos, fibromuscular dysplasia and pseudoxanthoma elasticum 5 6. The Barrow classification system further organises CCFs into four types based on angiographic features: type A CCFs are the most common and present as direct, high-flow communications between the internal carotid artery (ICA) and cavernous sinus1 2; type B, C and D dural CCFs are characterised as indirect and low-flow communications. Dural CCFs occur when connections are formed between the cavernous sinus and smaller arterial branches of the internal or ECA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations